A Brønsted base-promoted diastereoselective dimerization of azlactones - Pinheiro, Danielle L. J.; Batista, Gabriel M. F.; de Castro, Pedro P.; Flores, Leonã S.; Andrade, Gustavo F. S.; Amarante, Giovanni W. (Beilstein Journal of Organic Chemistry, 2017)
A novel Brønsted base system for the diastereoselective dimerization of azlactones using trichloroacetate salts and acetonitrile has been developed. Desired products were obtained in good yields (60–93%) and with up to >19:1 dr after one hour of reaction. Additionally, the relative stereochemistry of the major dimer was assigned as being trans, by X-ray crystallographic analysis. The kinetic reaction profile was determined by using 1H NMR reaction monitoring and revealed a second order overall kinetic profile. Furthermore, by employing this methodology, a diastereoselective total synthesis of a functionalized analogue of streptopyrrolidine was accomplished in 65% overall yield.
Keywords: azlactones; dimerization; diasteoreselective synthesis; kinetics; streptopyrrolidine analogue